A poeira, as pedras e a água : o programa um milhão de cisternas em Tobias Barreto-SE - Santos, Daisy Maria dos (2005)
This study has taken as reference, for investigation and analysis, the poor population access to water at the isolated areas in the semi-arid region of Tobias Barreto, which is located in the State of Sergipe, Brazil, from the experience of the Programa Um Milhão de Cisternas (P1MC) One Million Cisterns Program. The P1MC is a non state-owned public policy founded within the boundaries of the State reform, in the exhaustion of federal and state rural development vertical policies, in the persistence of rural Northeast underdevelopment problems, specially in the semi-arid region, and with the advent of sustainable development concept from 1992 on, at UNCED United Nations Conference on Environment and Development. Conceived in the methodological source derived from Áridas Project, it foresees an articulated action at the semi-arid territory with the objective of joining to its basic premises of breaking the monopoly of access to water, land and other means of production and preservation, sustainable use and environmental reconstitution of semi-arid natural resources, other public policies actions which are capable of supplying the bare necessities of that population such as education, health, work, land, environment, leisure, technology and welfare assistance. Guided by the effort of guaranteeing the principles of the Programa de Convivência com o Semi-árido Program of Coexistence with Semi-Arid, which proclaims joint management, partnership, decentralization and participation, social mobilization, citizen education, social rights, sustainable development, civil society strengthening and construction of a new political culture capable of breaking the command of favoritism and welfarism, P1MC faces, in Tobias Barreto, the challenges of the political weakness of the mass social organizations and the low level of organization of those who are socially excluded, in spite of their need of mobilization to get involved in the Program, in order to obtain their autonomy. This analysis has shown that the non-governamental organizations are subordinated to the determinations of programs that come to the localities ready, in accordance with international and multilateral organizations interests and without the participation of the population in their definition. In contradiction, their commitment and participation in the execution of the program are required. P1MC has been introduced in 6 of the 25 villages of Tobias Barreto municipality which were selected for beeing the most isolated ones, having the most difficult access to water and the highest level of poverty, reaching, in this way, 172 of the 283 families. The Program is inserted in the spectrum of water policies of sustainable regional development of poverty mitigation.